Study of Merkusii Pine Resin Using Aerial Photograph - Mohammadi Ichsan Setyowibowo (Forum Geografi, 1997)
This study is intended to find out the sap products of Pines mercusii Jungh at de Vries per are unit using variableness of the air photograph i.e. tree height, crown diameter and aree number per hectare. Its result analysis used regression analysis with the programe aid of SPSS for windows. The analysis outcome shows that, crown diameter tree height, relation between tree height and number of tree per hectare and relation between crown diameter and tree number per hectare, there are influence to the sap production per area unit. The formula mode isG = -418,963 + 534314 (D) – 1,316 (TH)2 + 0,142 (TH x NC) – 1,287 (D x NC)Where:       G     =     sap production (kg/hectare/15 days)                      TH   =     average tree height in meter                      D     =     average crown diameter in meter, and                      NC  =     tree number per hectare with determination cooeficien as 0,82, Aest of significant for 0,01 test level